Novel De-Acylative Ring Opening of 3-Acetyl and 3-Bromo Acetyl Coumarins - B. Yaragatti, Naazneen; V. Kulkarni, Manohar; N. A. Kumar, Gudibande; N. Gururow, Tayur (Letters in Organic Chemistry, 2012)
Reaction of 3-acetyl and 3-bromoacetyl coumarins with hydrazine hydrate has resulted in the ring opening of the coumarin moiety. The reaction was attempted with a view to obtain some new pyridazinones and pyrazolones. The reaction did not proceed via the expected pathway instead led to the formation of salicyl azines, the structure of which has been confirmed by single crystal X-ray studies.
Keywords: pyrazolones